The lives of the novel a history - Pavel, Thomas G. 1941- (Princeton University Press, 2013)
This is a boldly original history of the novel from ancient Greece to the vibrant world of contemporary fiction. Thomas Pavel argues that the driving force behind the novel's evolution has been a rivalry between stories that idealize human behavior and those that ridicule and condemn it. Impelled by this conflict, the novel moved from depicting strong souls to sensitive hearts and, finally, to enigmatic psyches. Pavel makes his case by analyzing more than a hundred novels from Europe, North and South America, Asia, and beyond. The result is a wide-ranging survey of the novel and a provocative reinterpretation of its development. -- Publisher website.